NEGOTIATING BETWEEN WORLDS: IDENTITY CRISIS AND CULTURAL DUALITY IN THE WORKS OF CONTEMPORARY INDIAN DIASPORIC WOMEN WRITERS - Nagpal, Sabia; Wadhwa, Poonam; Pant, Girish (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The experiences of Indian diasporic women writers reflect a profound negotiation between multiple cultural identities, leading to themes of identity crisis and cultural duality in their works. This paper explores how contemporary Indian diasporic women authors engage with questions of belonging, displacement, and self-definition. Through an analysis of selected works, the study highlights how these writers navigate their dual heritage, often balancing tradition with modernity, homeland with host nation, and personal agency with familial or societal expectations. The present paper is an honest attempt to attract the attention of the readers towards the Negotiating between Worlds: Identity Crisis and Cultural Duality in the Works of Contemporary Indian Diasporic Women Writers because their works address themes of alienation, hybridity, nostalgia, and redefinition of the self, often reflecting the tensions between cultural preservation and adaptation. The research scholar further writes that the literary narratives of authors such as Jhumpa Lahiri, Chitra Banerjee Divakaruni, Meena Alexander, Bharati Mukherjee, and Kiran Desai reveal the complex emotional and psychological struggles of women caught between two worlds. Additionally, the paper examines how gender plays a crucial role in shaping diasporic experiences, as women face unique challenges related to identity, tradition, and autonomy in a transnational context. By analyzing the literary techniques and thematic concerns of these authors, this paper contributes to the discourse on transnational feminism, cultural negotiations, and the evolving nature of identity in a globalized world.